2017
DOI: 10.1149/2.1051713jes
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Benefit in Employing Graded Electrodes for Lithium-Ion Batteries?

Abstract: Literature reports show both benefits and negligible impact when including graded electrodes in battery design, depending upon the exact model and conditions used. In this paper, we use two different optimization approaches for a secondary current distribution porous electrode model with nonlinear kinetics to confirm that computed solutions are correct. We use these confirmed optimal solutions to probe several ways that graded porosity can improve electrode performance. Single objective optimization such as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Using simulation, grading of the type explored here has been suggested to modify and homogenize the spatial distribution of the electrode overpotential [31]. The experimental work here provides cell data consistent with this prior suggestion and for the first time quantifies the marked benefits of grading by experiment.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 63%
See 1 more Smart Citation
“…Using simulation, grading of the type explored here has been suggested to modify and homogenize the spatial distribution of the electrode overpotential [31]. The experimental work here provides cell data consistent with this prior suggestion and for the first time quantifies the marked benefits of grading by experiment.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 63%
“…We expect that changing the local conductive carbon fraction may change the local electronic conductivity (and resistance), and thus may have a direct, homogenizing effect on the local overpotential and active material utilization. Some simulation-based studies have suggested this may be a promising line of enquiry [31], and building on recent developments in manufacturing capability for graded electrodes [28], we now investigate the effect of micro-scale composition grading in detail and in full cells. We design, manufacture and assess the performance of carefully controlled heterogeneous, graded electrode structures with the aim of promoting greater uniformity in overpotential distribution, and reaction rates across the electrode thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] In a recent study, Qi et al also optimized a cathode for reduced resistance. [ 38 ] However, they reported only a 4.4% resistance reduction.…”
Section: Pathways Toward Optimal Electrode Designmentioning
confidence: 99%
“…Focusing on the minimization of the ohmic resistance of a porous electrode, Ramadesigan et al [25] optimized a spatially varying porosity profile. Qi et al [26] applied a multi-objective optimization to a layered porosity profile for optimally balancing the ohmic resistance, the average overpotential and the standard deviation of the overpotential.…”
Section: Introductionmentioning
confidence: 99%